Research on Modeling and the Operation Strategy of a Hydrogen-Battery Hybrid Energy Storage System for Flexible Wind Farm Grid-Connection - Wen, Ting; Zhang, Zheyuan; Lin, Xiangning; Li, Zhengtian; Chen, Chong; Wang, Zhixun (IEEE access, 2020)
Energy storage systems used for the flexible grid connection of wind farms in terms of minute time-scale usually consist of batteries. Due to the capacity constraints of batteries, when wind energy fluctuations exceed limits continuously, this type of energy storage system topology cannot present good performance. To solve this problem, this paper introduces a hybrid energy storage system (HESS) topology consisting of batteries and a hydrogen conversion system (HCS). To achieve a flexible wind farm grid connection with a minimum energy loss, a HESS control strategy is proposed to make full use of the advantages of the HCS capacity and battery energy conversion efficiency. The optimization goal is to minimize power fluctuations, battery life consumption, and energy loss. The energy conversion characteristics of the flexible wind farm grid-connection system are also analyzed. The simulation results show that compared with other strategies using only batteries, the operating strategy using the HESS with the same cost can combine the advantages of the battery efficiency and HCS power continuity to achieve a balance between the controlling energy loss and smoothing power fluctuations.